JUDICIAL REFORM IN SERBIA AND NEGOTIATING CHAPTER 23 - A CRITICAL OUTLOOK - Reljanović, Mario; Knežević Bojović, Ana (Pravni zapisi, 2014)
A sound and independent judiciary is a precondition for accomplishing the rule of law. Sound judiciary and citizens’ trust in it are of critical importance in any state. However, the attainment of true judicial independence is a task faced both by old democracies and transition countries. For countries facing the challenge of EU accession, such as Serbia, good judiciary is not only an immanent value to be obtained, but will also be a key issue during the negotiation process. Since the adoption of the new constitutional framework in 2006, Serbia has embarked on the task of improving its judicial system. Unfortunately, this process was carried out under strong political influences, and has had a devastating effect on the Serbian judicial corps, at the same time undermining any trust citizens had in the judicial force. Following the change of the political majority in the Parliament and the changes in government, the Serbian Ministry of Justice has undertaken the task of formulating a new Judicial Reform Strategy and Action Plan for its implementation, which are be the core instruments used in the attempt to attain the two above-mentioned objectives: establishing sound and independent judiciary and meeting the relevant EU accession benchmarks. In this paper, the authors will provide their critical account of the Serbian National Judicial Reform Strategy 2013-2018 and the Action Plan for its Implementation, identifiying its major deficiencies and drawbacks. The authors will also analyse the planned and implemented changes to the Serbian regulatory framework.